Imaging of Intracranial Aneurysms: A Review of Standard and Advanced Imaging Techniques - Sricharan S. Veeturi; Samuel Hall; Soichiro Fujimura; Mahmud Mossa-Basha; Elena Sagues; Edgar A. Samaniego; Vincent M. Tutino (Translational Stroke Research, 2025)

Development of 3D-iNET ORION: a novel, pre-clinical, three-dimensional in vitro cell model for modeling human metastatic neuroendocrine tumor of the pancreas - Jan Strnadel; Mark A. Valasek; Grace Y. Lin; Huahui Lin; Ann M. Ponsford Tipps; Sang Myung Woo; Ken Fujimura; Huawei Wang; Sunkyu Choi; Jack Bui; Christopher Hermosillo; Kristen Jepsen; et al. (Human Cell, 2024)
Neuroendocrine tumors (NETs) of the pancreas are rare neoplasms that present complex challenges to diagnosis and treatment due to their indolent course. The incidence of pancreatic neuroendocrine tumors has increased significantly over the past two decades. A limited number of pancreatic neuroendocrine cell lines are currently available for the research. Here, we present 3D-iNET ORION, a novel 3-dimensional (spheroid) cell line, isolated from human pancreatic neuroendocrine tumor liver metastasis. Three-dimensionally grown (3D) cancer cell lines have gained interest over the past years as 3D cancer cell lines better recapitulate the in vivo structure of tumors, and are more suitable for in vitro and in vivo experiments. 3D-iNET ORION cancer cell line showed high potential to form tumorspheres when embedded in Matrigel matrix and expresses synaptophysin and EpCAM. Electron microscopy analysis of cancer cell line proved the presence of dense neurosecretory granules. When xenografted into athymic mice, 3D-iNET ORION cells produce slow-growing tumors, positive for chromogranin and synaptophysin. Human Core Exome Panel Analysis has shown that 3DiNET ORION cell line retains the genetic aberration profile detected in the original tumor. In conclusion, our newly developed neuroendocrine cancer cell line can be considered as a new research tool for in vitro and in vivo experiments.

Mortality risk factors and fulminant sub-phenotype in anaerobic bacteremia: a 10-year retrospective, multicenter, observational cohort study - Kentaro Nagaoka; N. Iwanaga; Y. Takegoshi; Y. Murai; H. Kawasuji; M. Miura; Y. Sato; Y. Hatakeyama; H. Ito; Y. Kato; N. Shibayama; Y. Terasaki; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Multiple Aneurysms AnaTomy CHallenge 2018 (MATCH): Phase I: Segmentation - Philipp Berg; Samuel Voß; Sylvia Saalfeld; Gábor Janiga; Aslak W. Bergersen; Kristian Valen-Sendstad; Jan Bruening; Leonid Goubergrits; Andreas Spuler; Nicole M. Cancelliere; David A. Steinman; Vitor M. Pereira; et al. (Cardiovascular Engineering and Technology, 2018)

Critical Information Gaps Impeding Understanding of the Role of Larval Connectivity Among Coral Reef Islands in an Era of Global Change - Peter J. Edmunds; Shelby E. McIlroy; Mehdi Adjeroud; Put Ang; Jessica L. Bergman; Robert C. Carpenter; Mary A. Coffroth; Atsushi G. Fujimura; James L. Hench; Sally J. Holbrook; James J. Leichter; Soyoka Muko; et al. (Frontiers in Marine Science, 2018)

Transplantation of Human-Induced Pluripotent Stem Cell-Derived Neural Precursors into Early-Stage Zebrafish Embryos - J. Strnadel; H. Wang; C. Carromeu; A. Miyanohara; K. Fujimura; E. Blahovcova; V. Nosal; H. Skovierova; R. Klemke; E. Halasova (Journal of Molecular Neuroscience, 2018)

Trigonelline and related nicotinic acid metabolites: occurrence, biosynthesis, taxonomic considerations, and their roles in planta and in human health - Hiroshi Ashihara; Iziar A. Ludwig; Riko Katahira; Takao Yokota; Tatsuhito Fujimura; Alan Crozier (Phytochemistry Reviews, 2015)

Fine-scale features on the sea surface in SAR satellite imagery – Part 2: Numerical modeling - S. Matt; A. Fujimura; A. Soloviev; S. H. Rhee; R. Romeiser (Ocean Science, 2014)
With the advent of the new generation of synthetic aperture radar (SAR) satellites, it has become possible to resolve fine-scale features on the sea surface on the scale of meters. The proper identification of sea surface signatures in SAR imagery can be challenging, since some features may be due to atmospheric distortions (gravity waves, squall lines) or anthropogenic influences (slicks), and may not be related to dynamic processes in the upper ocean. In order to improve our understanding of the nature of fine-scale features on the sea surface and their signature in SAR, we have conducted high-resolution numerical simulations combining a three-dimensional non-hydrostatic computational fluid dynamics model with a radar imaging model. The surface velocity field from the hydrodynamic model is used as input to the radar imaging model. The combined approach reproduces the sea surface signatures in SAR of ship wakes, low-density plumes, and internal waves in a stratified environment. The numerical results are consistent with observations reported in a companion paper on in situ measurements during SAR satellite overpasses. Ocean surface and internal waves are also known to produce a measurable signal in the ocean magnetic field. This paper explores the use of computational fluid dynamics to investigate the magnetic signatures of oceanic processes. This potentially provides a link between SAR signatures of transient ocean dynamics and magnetic field fluctuations in the ocean. We suggest that combining SAR imagery with data from ocean magnetometers may be useful as an additional maritime sensing method. The new approach presented in this work can be extended to other dynamic processes in the upper ocean, including fronts and eddies, and can be a valuable tool for the interpretation of SAR images of the ocean surface.

Sialyl-glycoconjugates in cholesterol-rich microdomains of P388 cells are the triggers for apoptosis induced by Rana catesbeiana oocyte ribonuclease - Y. Ogawa; S. Sugawara; T. Tatsuta; M. Hosono; K. Nitta; Y. Fujii; H. Kobayashi; T. Fujimura; H. Taka; Y. Koide; I. Hasan; R. Matsumoto; et al. (Glycoconjugate Journal, 2014)

Contamination and impacts of new antifouling biocide Irgarol-1051 on subtropical coral reef waters - M. A. Sheikh; T. Higuchi; H. Fujimura; T. S. Imo; T. Miyagi; T. Oomori (International Journal of Environmental Science and Technology, 2009)

Lunar-A mission: Outline and current status - H. Mizutani; A. Fujimura; S. Tanaka; H. Shiraishi; T. Nakjima (Journal of Earth System Science, 2005)

Positional cloning of the rice Rf-1 gene, a restorer of BT-type cytoplasmic male sterility that encodes a mitochondria-targeting PPR protein - H. Akagi; A. Nakamura; Y. Yokozeki-Misono; A. Inagaki; H. Takahashi; K. Mori; T. Fujimura (Theoretical and Applied Genetics, 2004)

Micron, a microsatellite-targeting transposable element in the rice genome - H. Akagi; Y. Yokozeki; A. Inagaki; K. Mori; T. Fujimura (Molecular Genetics and Genomics, 2001)

Influence of diltiazem on the pharmacokinetics of amlodipine in elderly hypertensive patients - M. Sasaki; A. Maeda; A. Fujimura (European Journal of Clinical Pharmacology, 2001)

The H-cadherin ( CDH13 ) gene is inactivated in human lung cancer - Masami Sato; Yuriko Mori; Akira Sakurada; Shigefumi Fujimura; A. Horii (Human Genetics, 1998)

Pharmacokinetic alterations of quinapril during repeated treatment in elderly subjects - M. Sasaki; A. Maeda; A. Fujimura (European Journal of Clinical Pharmacology, 1998)

Effect of omeprazole and cimetidine on plasma aldosterone response to angiotensin II - M. Sasaki; A. Maeda; A. Fujimura (European Journal of Clinical Pharmacology, 1998)

Effects of dopamine on veins in humans: comparison with noradrenaline and influence of age - K. Harada; M. Ohmori; Y. Kito; A. Fujimura (European Journal of Clinical Pharmacology, 1998)

Comparison of venodilatory effect of nicardipine, diltiazem, and verapamil in human subjects - K. Harada; M. Ohmori; K. Sugimoto; A. Fujimura (European Journal of Clinical Pharmacology, 1998)

Highly polymorphic microsatellites of rice consist of AT repeats, and a classification of closely related cultivars with these microsatellite loci - H. Akagi; Y. Yokozeki; A. Inagaki; T. Fujimura (Theoretical and Applied Genetics, 1997)